(untitled) (translation. a transdisciplinary journal, 2022)
If, as Nietzsche argues, any attempt at mastering a text, or the world as text, “involves a fresh interpretation, an adaptation through which any previous ‘meaning’ and ‘purpose’ are necessarily obscured or even obliterated” (1969:12), the implicit relationship that is usually established between authors and interpreters is not exactly inspired by cooperation or collaboration, as common sense and the essentialist tradition would have it but, rather, is constituted by an underlying competition, by a struggle for the power to determine that which will be (provisionally) accepted as true and definite within a certain context and under certain circumstances.